2010
DOI: 10.1088/0031-8949/82/03/035601
|View full text |Cite
|
Sign up to set email alerts
|

Effect of precursor concentrations on structural, microstructural and optical properties of nanocrystalline ZnO powder synthesized by an ultrasonic atomization technique

Abstract: In this paper, we report on the effect of concentration on nanocrystalline ZnO powder prepared by an ultrasonic atomization technique, which is a promising method because of its simplicity, inexpensiveness and safety. The morphology and size of ZnO nanocrystallites associated with nanopowder were characterized by transmission electron microscopy (TEM). It revealed that the powder consisted of nanocrystallites with grain sizes between 8 and 15 nm. These values match the grain sizes (8–14 nm) calculated from x-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…where ρ is the solution density, f is the spraying frequency, and 𝑤 is the surface tension of the solution, which depends on the ZN concentration. Such dimensions can be easily calculated using the parameter 𝑤 according to [7]. In turn, such calculations are in good agreement with the size of the powder granules obtained using an electron microscope (Fig.…”
Section: Experimental Partsupporting
confidence: 75%
See 1 more Smart Citation
“…where ρ is the solution density, f is the spraying frequency, and 𝑤 is the surface tension of the solution, which depends on the ZN concentration. Such dimensions can be easily calculated using the parameter 𝑤 according to [7]. In turn, such calculations are in good agreement with the size of the powder granules obtained using an electron microscope (Fig.…”
Section: Experimental Partsupporting
confidence: 75%
“…Thus, in [6], it was shown that during the synthesis of ZnO NCs by the USP method at T = 500⁰C, a decrease in the concentration of zinc nitrate (ZN) from 10 % to 1 % causes a change in the size of NCs, namely, a decrease in size from 55 nm to 23 nm. The synthesis of ZnO from a solution of zinc acetate with a concentration of 0.3 % (0.01M) allows to obtain NCs with a size of 15 nm [7]. Also, the possibility of reducing the size of ZnONCs by reducing the concentration of ZN was shown in [8].…”
Section: Introductionmentioning
confidence: 99%
“…The nanocrystalline ZnO powder was prepared by ultrasonic atomization and decomposition technique, the procedure of which has been explained elsewhere [10]. The thixotropic paste of nanocrystalline zinc oxide powder was formulated and thick films were prepared using screen printing technique on glass substrate in the desired pattern explain elsewhere [11].…”
Section: Experimental Preparation Of Nanocrystalline Zno Powder and Tmentioning
confidence: 99%